Survival rates of short dental implants (≤6 mm) compared with implants longer than 6 mm in posterior jaw areas: A meta‐analysis. (17th October 2018) - Papaspyridakos, Panos; De Souza, Andre; Vazouras, Konstantinos; Gholami, Hadi; Pagni, Sarah; Weber, Hans‐Peter
Abstract: Purpose: To systematically review randomized controlled clinical trials (RCTs) reporting on the long‐term survival and failure rates, as well as the complications of short implants (≤6 mm) versus longer implants (>6 mm) in posterior jaw areas. Materials and Methods: Electronic and manual searches were conducted to identify studies, specifically RCTs, reporting on short dental implants (≤6 mm) and their survival and complication rates compared with implants longer than 6 mm. Secondary outcomes analyzed were marginal bone loss and prosthesis survival rates. Results: Ten RCTs fulfilled the inclusion criteria and featured a total of 637 short (≤6 mm) implants placed in 392 patients, while 653 standard implants (>6 mm) were inserted in 383 patients. The short implant survival rate ranged from 86.7% to 100%, whereas standard implant survival rate ranged from 95% to 100% with a follow‐up from 1 to 5 years. The risk ratio (RR) for short implant failure compared to standard implants was 1.29 (95% CI: 0.67, 2.50, p = 0.45), demonstrating that overall, short implants presented higher risk of failure compared to longer implants. The heterogeneity test did not reach statistical significance ( p = 0.67), suggesting low between‐study heterogeneity. The prosthesis survival rates from the short implant groups ranged from 90% to 100% and from 95% to 100% for longer implant groups, respectively. Conclusion: Short implants (≤6 mm) were found to have higher variability and lower predictability in survival rates compared to longer implants (>6 mm) after periods of 1–5 years in function. The mean survival rate was 96% (range: 86.7%–100%) for short implants, and 98% (range 95%–100%) for longer implants. Based on the quantity and quality of the evidence provided by 10 RCTs, short implants with ≤6 mm length should be carefully selected because they may present a greater risk for failure compared to implants longer than 6 mm.